MRI findings predict radiographic progression and development of erosions in hand osteoarthritis. Issue 1 (9th September 2014) - Haugen, Ida K; Slatkowsky-Christensen, Barbara; Bøyesen, Pernille; Sesseng, Sølve; van der Heijde, Désirée; Kvien, Tore K
Abstract : Objectives: To examine whether MRI features predict radiographic progression including erosive evolution in patients from the Oslo hand osteoarthritis (OA) cohort, which is the first longitudinal hand OA study with available MRI. Methods: We included 74 patients (91% female, mean (SD) age of 67.9 (5.3) years) with MRI of the dominant hand and conventional radiographs taken at baseline and 5-year follow-up. Baseline MRIs were read according to the Oslo hand OA MRI score. We used three definitions of radiographic progression: Progression of joint space narrowing (JSN, grades 0–3), increased Kellgren–Lawrence score (grades 0–4) or incident erosions (absent/present). For each definition, we examined whether MRI features predicted radiographic progression in the same joint using Generalised Estimating Equations. We adjusted for age, sex, Body Mass Index, follow-up time and other erosive joints (the latter for analyses on incident erosions only). Results: MRI-defined moderate/severe synovitis (OR=3.52, 95% CI 1.29 to 9.59), bone marrow lesions (BML) (OR=2.73, 95% CI 1.29 to 5.78) and JSN (severe JSN: OR=11.05, 95% CI 3.22 to 37.90) at baseline predicted progression of radiographic JSN. Similar results were found for increasing Kellgren–Lawrence score, except for weaker association for JSN. Baseline synovitis, BMLs, JSN, bone damage, osteophytes and malalignment were significantly associated with development of radiographic erosions, of which malalignment showed the strongest association (OR=10.18, 95% CI 2.01 to 51.64). Conclusions: BMLs, synovitis and JSN were the strongest predictors for radiographic progression. Malalignment was associated with incident erosions only. Future studies should explore whether reducing BMLs and inflammation can decrease the risk of structural progression.